(untitled) (American Journal of Economics and Business Innovation, 2025)
This study investigated between online advertisement and online purchase intention among Bangladesh domestic tourists, especially the moderating effect of trust. The study was based on Theory of Planned Behavior (TPB) framework, and the aim of the study evaluated consumer behavioral intention with regard to domestic tourism. The study was a quantitative and a cross-sectional research design. The results were obtained by conducting a structured questionnaire handed out among 390 domestic tourists whose sample was taken using simple random sampling. The SPSS and SmartPLS statistics were used where the study hypotheses were sore tested by the structural equation model (SEM). The results showed that there was a significant positive correlation between online advertisement and purchase intention online. In addition, the level of trust did not contribute significantly to this relationship, meaning that familiarity with digital devices decreases the level of trust in the context of online purchases made by domestic tourists. The study contributes theoretically by demonstrating that, in emerging markets such as Bangladesh, effective online advertising can directly drive consumer purchase intention. Practically, the results suggest that marketers should pay more attention to the quality and creativity of the advertisement instead of focusing merely on establishing trust. The study provides limitations and future research.